Conceptualizing employee identification with sport organizations: Sport Employee Identification (SEI). Issue 4 (November 2015) - Oja, Brent D.; Bass, Jordan R.; Gordon, Brian S.
Highlights: We propose an organizational identification model for sport employees. The theoretical model is based on past studies and ethnographic data. Three antecedent categories are posited to influence Sport Employee Identification. Meets the call from scholars arguing for additional sport specific constructs. Abstract: The concepts of organizational identification and team identification have been researched heavily over the last half-century. However, scholars have failed to specifically examine organizational identification among sport employees. We develop a theoretical framework of organizational identification of sport employees, coined Sport Employee Identification (SEI). We conceptualize SEI as an amalgamation of organizational identification and team identification in which sport employees are both external (fans) and internal (employee) members of the sport organization. The development of the SEI model is based on related theory and further ethnographic data are collected over a four-month period within an intercollegiate athletics fundraising department. Implications for scholars and practitioners and avenues for future research are discussed.